New horizons in rib fracture management in the older adult. (20th December 2019) - Coary, Roisin; Skerritt, Conor; Carey, Anthony; Rudd, Sarah; Shipway, David
Abstract: Adults aged ≥60 years now represent the majority of patients presenting with major trauma. Falls are the most common cause of injury, accounting for nearly three-quarters of all traumas in this population. Trauma to the thorax represents the second most common site of injury in this population, and is often associated with other serious injuries. Mortality rates are 2–5 times higher in older adults compared to their younger counterparts, often despite equivalent injury severity scores. Risk scoring systems have been developed to identify rib fracture patients at high risk of deterioration. Overall mortality from rib fractures is high, at approximately 10% for all ages. Mortality and morbidity from rib fractures primarily derive from pain-induced hypoventilation, pneumonia and respiratory failure. The main goal of care is therefore to provide sufficient analgesia to allow respiratory rehabilitation and prevent pulmonary complications. The provision of analgesia has evolved to incorporate novel regional anaesthesia techniques into conventional multimodal analgesia. Analgesia algorithms may aid early aggressive management and escalation of pain control. The current role for surgical fixation of rib fractures remains unclear for older adults who have been underrepresented in the research literature. Older adults with rib fractures often have multi-morbidity and frailty which complicate their injuries. Trauma services are evolving, and increasingly geriatricians will be embedded into trauma services to deliver comprehensive geriatric assessment. This review aims to provide an evidence-based overview of the management of rib fractures for the physician treating older patients who have sustained trauma.